THE INFLUENCE OF PUZZLE GAMES ON THE COLLABORATIVE ABILITY OF CHILDREN AGED 5-6 YEARS IN THE PEMBINA STATE KINDERGARTEN IN SUNGAI FULL CITY - Thezy Meilevia Wijayanti Thezy (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research is based on the fact that there is still a lack of cooperative abilities in children aged 5-6 years. This can be seen from the fact that there are still many children who do not want to play and share toys together, there is still a lack of variety of activities carried out to develop cooperation among children in kindergarten. Cooperation skills in children really need to be taught from an early age, children learn through playing, using puzzle media can improve children’s cooperation abilities. The aim of this research is to determine the effect of puzzle gemes on the cooperative abilities of children aged 5-6 years at the Pembina State Kindergarten, Sungai Penuh City. This research is a type of quantitative research that uses experimental methods. This researcj includes Pre-Experimental Design. The population of this study consisted of 16 children. The sample for this study consisted of 16 children from the entire population who were selected using saturated sampling. The data collection technique used in this research uses observation. The data analysis technique used in this research is the t test. Based on the research results obtained, the t table value is 1.7531, while the t value obtained is 8.91942, so t > t, this means that there is an influence of puzzle games on the cooperative abilities of children aged 5-6 years at the Pembina State Kindergarten, Sungai Penuh City.